Rehabilitation of patients after surgical treatment of pulmonary tuberculosis in a specialized sanatorium - R. V. Tarasov; E. V. Krasnikova; D. F. Gorlov; M. I. Chushkin; M. A. Bagirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Actuality. Surgery for patients with pulmonary tuberculosis should be accompanied by a complex of rehabilitation measures with an algorithm for the formation of rehabilitation programs depending of the patients functional state and of volume of surgical intervention.Aim: to study the effectiveness of rehabilitation measures depending on the degree of functional impairments considering the volume of surgical interventions in patients operated on for advanced destructive pulmonary tuberculosis.Object and methods. The study included 109 patients who were divided into 4 groups: group 1 – with lung resections and segmentectomies (73 people), group 2 – with bilateral staged atypical lung resections in combination with unilateral delayed thoracoplasty (14 people), group 3 – with lobectomies and bisegmentectomies (13 people),  group 4 – with pneumonectomies (9 people). A rehabilitation program was compiled for each observed group. The effectiveness of rehabilitation measures was assessed by spirometry, oxygen saturation, goniometry, visual analog pain scale (VAS), Borg CR10 scale, mMRC dyspnea scale.Results. In each study group, changes in lung function indicators were observed, in groups 1-3, the indicators of VC; FEV1; FEV1/VC — the Index Tiffeneau (IT) changed, in group 4, significant changes were only from IT. The severity of shortness of breath on the mMRC scale and the severity of perceived stress on the Borg CR10 scale decreased in each group. The intensity of the pain syndrome decreased in each study group according to VAS.Conclusion. Rehabilitation of patients who have undergone surgery of pulmonary tuberculosis in a specialized sanatorium becomes more effective and achieving positive recovery results with the use of rehabilitation programs, depending on the severity of functional disorders of patients and different volumes of surgical intervention.